Material witness: the imaging of historical sites. Issue 3 (3rd July 2017) - Smiles, Sam
Abstract: This article examines artists' attempts to recuperate a sense of historical process and temporality in the material objects they scrutinized. In the later eighteenth and early nineteenth centuries innovative visual approaches were developed that privileged the inspection and recording of material evidence where traces of historical alterations could be found. Such careful attention to historical sequence necessarily opposed an understanding of identity whose concentration on function and purpose transcended the vicissitudes of time. This visualization of the materiality of history was aided by three principal graphic devices: textual inscription, differentiated sequence, and notated palimpsest. Referring to Thomas Patch, William Stukeley, Giovanni Battista Piranesi, and John Carter, examples are provided of their records of alterations to works of art, monuments, and built structures. Their several approaches are located within broader discussions of temporality, memory, and change.